2014
DOI: 10.1186/s12929-014-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of novel cognitive enhancer noopept on AD-related cellular model involves the attenuation of apoptosis and tau hyperphosphorylation

Abstract: BackgroundNoopept (N-phenyl-acetyl-L-prolylglycine ethyl ester) was constructed as a dipeptide analog of the standard cognition enhancer, piracetam. Our previous experiments have demonstrated the cognition restoring effect of noopept in several animal models of Alzheimer disease (AD). Noopept was also shown to prevent ionic disbalance, excitotoxicity, free radicals and pro-inflammatory cytokines accumulation, and neurotrophine deficit typical for different kinds of brain damages, including AD. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
(48 reference statements)
0
10
0
2
Order By: Relevance
“…It is of interest to note that during this study the administration of Noopept not only reduced spinal Iba1 level, as a microglial activity marker, but also reduced microglia dependent BDNF and pro-BDNF expression levels in the lumbar part of the spinal cord. Although there are considerable studies on the anti-inflammatory effect of Noopept [28,61], the current study stated the novel dipeptide anti-hyperalgesic and anti-inflammatory effects were mediated via inhibition of microglia activity and apoptosis. Ostrovskaya et al showed that Noopept, through normalizing incretin system parameters, had an anti-apoptotic effect on pancreatic β cells in the context of experimental Diabetes [63], and in another study they indicated neuroprotective effects [64].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is of interest to note that during this study the administration of Noopept not only reduced spinal Iba1 level, as a microglial activity marker, but also reduced microglia dependent BDNF and pro-BDNF expression levels in the lumbar part of the spinal cord. Although there are considerable studies on the anti-inflammatory effect of Noopept [28,61], the current study stated the novel dipeptide anti-hyperalgesic and anti-inflammatory effects were mediated via inhibition of microglia activity and apoptosis. Ostrovskaya et al showed that Noopept, through normalizing incretin system parameters, had an anti-apoptotic effect on pancreatic β cells in the context of experimental Diabetes [63], and in another study they indicated neuroprotective effects [64].…”
Section: Discussionmentioning
confidence: 68%
“…Our observations in the second step of the study suggested that the long-term administration of Noopept during persistent peripheral inflammation not only decreases the activity of spinal microglia but also decreases microglia dependent BDNF and pro-BDNF expressions in parallel with thermal hyperalgesia and dorsal horn cell apoptosis. Despite the many studies done on the effects of Nootropics, such as Noopept, on cognitive disorders like Attention-Deficit/Hyperactivity Disorder (ADHD), Alzheimer's and Parkinson's diseases [61,62], the mechanism of the effect of this novel dipeptide on persistent inflammatory pain and its involved central mechanisms remained largely uncharacterized. Our results demonstrated that Noopept treatment was not only effective in reducing pain behaviors but also reduced spinal cell apoptosis, which is related to pain behavior variations in the context of CFA-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Following the ability of Noopept to increase animal survival in hyperbaric hypoxia [ 37 ] detected at the beginning of the study of this dipeptide, it has been shown that it reduces the volume of ischemic brain damage in circulatory hypoxia models: for example, cortical photochemically induced thrombosis [ 6 ] and ligation of the middle artery [ 5 ]. The ability of Noopept to attenuate the severity of oxidative stress was established in neuronal cultures of various types: granular cerebellar cells [ 35 ], cortical neuron culture of aborted fetuses with diagnosed Down syndrome [ 7 ], PC12 culture [ 38 ], SH-SY5Y culture [ 39 ], and in vivo experiments on brain tissue and rat plasma [ 40 ]. The ability to enhance superoxide dismutase and catalase activity was shown both in the experiment [ 10 ] and in clinical conditions [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of Noopept not only to eliminate the manifestations of cognitive deficit [ 41 ], but to exert also a neuroprotective effect was shown in models of Alzheimer’s disease: it attenuated the disturbance of oxidative processes and calcium homeostasis, enhanced neurogenesis, prevented the tau protein aggregation caused by a fragment of β-amyloid 25-35 [ 38 ], and eliminated NGF and BDNF deficit caused by diabetogenic toxin streptozotocin administration into brain ventricles [ 42 ]. Noopept is capable of reducing the cytotoxic effect of aggregated α-synuclein in a cell model of Parkinson’s disease [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, Piracetam exerts its neuroprotective effects on PC12 cells, SH-SY5Y cells, and SH-SY5Y APPwt cells by improving synaptic plasticity, maintaining mitochondrial dynamic and neuritogenesis 58 . In addition, Noopept protects PC12 cells against Aβ25-35 induced toxicity by inhibiting of oxidative damage, preventing of calcium overload, suppressing apoptosis, attenuating hyperphosphorylation of tau, and ameliorating the neural outgrowth induced by Aβ25-35 59 . In addition to the preclinical studies, several clinical trials were also conducted on nootropics in AD patients and related dementias with impressive results.…”
Section: Nootropicsmentioning
confidence: 99%